Hormonal Profile and Efficacy of Long Pulse Nd-YAG Laser in Treatment of Hirsutism - Karn, D; KC, S; Timalsina, M; Gyawali, P (Journal of Nepal Health Research Council, 2014)
Background: Hormones, particularly androgens play a vital role in hair growth, differentiation and distribution. Hirsutism is a common entity among Nepalese population with skin types III, IV and V. Long pulsed lasers are commonly used for hair removal. Methods: This is a prospective analytical study done in Dhulikhel Hospital Kathmandu University Hospital, Kavre, Nepal from November 2010 to November 2011. Patients were first subjected to hormonal evaluation. Androgens, their tropic hormones, insulin resistance markers and endocrine components were measured and compared. Subjects were then categorized into two groups according to androgen levels: group A (n=30) with significantly high androgen (total testosterone and dehydroepiandrosterone sulfate) or elevated luteinizing hormone: follicle stimulating hormone ratio, consistent with Polycystic Ovarian Syndrome (PCOS) and group B (n=30). Adrenal tumour was ruled out in all patients. All patients received long pulse Nd-YAG laser (50J/cm2; 50 msec pulse duration) therapy at four weeks interval to achieve at least 50% hair reduction. Results: Among group A patients, average 8.1 treatment sessions were required for substantial hair reduction, whereas, average 5.7 sessions produced similar results in group B patients (p-value <0.05). Conclusions: Patients with high androgen level and elevated LH: FSH ratio requires more treatment sessions for hair removal with long pulsed ND-YAG laser than patients with normal or low hormone level. Keywords: hair removal; hormones; Nd-YAG laser; polycystic ovary syndrome.